Effect of N-methyl-D-aspartate-receptor-enhancing agents on cognition in patients with schizophrenia: A systematic review and meta-analysis of double-blind randomised controlled trials. (April 2019) - Chang, Chun-Hung; Lane, Hsien-Yuan; Tseng, Ping-Tao; Chen, Shaw-Ji; Liu, Chieh-Yu; Lin, Chieh-Hsin
Background: Multiple N-methyl-d -aspartate (NMDA)-receptor-enhancing agents have demonstrated promising effects for cognition in schizophrenia. However, the results of studies have been conflicting. This updated meta-analysis explored the effect of NMDA-receptor-enhancing agents on cognitive function. Methods: We searched PubMed, the Cochrane Collaboration Central Register of Controlled Clinical Trials and Cochrane Systematic Reviews for studies on the effect of NMDA-receptor-enhancing agents on cognitive function in patients with schizophrenia up to September 2018. Double-blind randomised placebo trials with cognition rating scales were included. We pooled studies by using a random-effect model for comparisons with add-on NMDA-receptor-enhancing agents. Cognitive function scores were compared between baseline and subsequent levels, and NMDA-receptor-positive modulators were assessed using the standardised mean difference (SMD) with 95% confidence intervals (CIs). We evaluated statistical heterogeneity through visual inspection of funnel plots and by using the I 2 statistic. Results: We identified 25 trials with 1951 participants meeting the inclusion criteria. NMDA-receptor-enhancing agents had a small but nonsignificant effect compared with the placebo on overall cognitive function (SMD = 0.068, CI = −0.056 to 0.193, P  = 0.283). We identified trials enrolling patients aged between 30 and 39 years old, which reported significant positive effects (SMD: 0.163, 95% CI: 0.016–0.310, P  = 0.030). Men were associated with a smaller effect of NMDA-receptor-positive modulators on overall cognitive function. Moreover, subgroup meta-analysis of cognitive domains revealed that N-acetyl cysteine (NAC) had a significant effect on working memory ( P -value for interaction = 0.038; SMD = 0.679, CI = 0.397–0.961, P  < 0.001). Conclusions: Our meta-analysis revealed no significant effect of NMDA-enhancing agents on overall cognition. However, subgroup analysis suggested that NMDAR-enhancing agents may benefit young patients with schizophrenia, and NAC may have an effect on working memory. Additional trials with larger samples are suggested to evaluate these cognitive domains and ascertain the possible mechanisms.